Families of Hymenopteran parasitoids in organic coffee cultivation in Santo Antônio do Amparo,MG , Brazil. - Ferreira, Fabricio Zelesnikar; Silveira, Luís Cláudio Paterno; Haro, Marcelo Mendes (Coffee Science - ISSN 1984-3909, 2013)
The objective of this study was to understand the profiles of families of Hymenoptera parasitoids present in the organic coffee grown in Santo Antônio do Amparo, Brazil. Samples were collected monthly to calculate the accumulation curve, richness and abundance indices. 4817 parasitoids distributed in nine families and 26 superfamilies were collected. The superfamily Chalcidoidea had the highest abundance (28.34 %) and diversity (13 families). Families that have natural enemies to the coffee pests represented 42 % of arthropods collected. Samples were taken of Parasitoid families not related to coffee pests, indicating the importance of organic farming in the conservation of hymenoptera.